Chewing Khat Transmission Dynamics: A Mathematical Model and Stability Analysis - Abayneh Kebede Fantaye; Zerihun Kinfe Birhanu (Journal of Applied Mathematics)
In this study, the authors proposed a nonlinear deterministic model and stability analysis for the transmission dynamics of chewing khat. The model’s solution is proved to be positive and bounded, and the basic reproduction number (R0) is calculated using the next-generation matrix method. Following that, the authors have looked at the local and global stability of the model’s khat-free and endemic equilibrium points. When R0<1, the chewing khat-free equilibrium point is locally and globally asymptotically stable, whereas when R0>1, the endemic equilibrium point is locally and globally asymptotically stable. The simulation results demonstrate the analytical results.